Efecto de tres niveles de inclusión de Trichanthera gigantea en dietas sobre parámetros digestivos en pollos finqueros - Guerrero Sisalima, Santiago Xavier (2024)
In recent years in Ecuador, a segment of the market has been inclined towards the consumption of free-range chicken meat as it is considered more natural and has better flavor, qualities framed in considerations of the breed, such as slow growth; the feed item generates meaningful costs, making it paramount to look for new alternative raw materials to lower these production costs. This study's research paperwork aims to determine the effect of three levels of Trichanthera gigantea inclusion in diets on digestive parameters in broiler chickens. We used 150 broiler chickens from 29 to 71 days of age randomly distributed in three treatments 0%, 5%, and 10% of Trichanthera gigantea; the study variables were absolute and relative weight and length of the total digestive tract, small intestine, gizzard, and caecal pH. Data were analyzed in InfoStat software, applying an analysis of variance (ANOVA) and an LSD Fisher test to compare means. There was a trend in the absolute weight of the total digestive tract (p=0.065); there was no statistical difference in the absolute and relative weight (p=0.217) of the small intestine, gizzard, and caecum. Digestive tract length was not significant (p=0.370), but the T2 treatment (10%) had greater absolute (200.60 cm) and relative (11.85%) length. There was no difference in cecum pH (p=0.966). We concluded that the levels of Trichanthera gigantea in diets did not affect the digestive parameters., However, we evidenced a greater length of the gastrointestinal tract with the highest level of inclusion.